Artificial Intelligence Experts' Perceptions on the Effective Use of Artificial Intelligence Applications in University Learning Environments - AlAli, Rommel Mahmoud; Al-Barakat, Ali Ahmad (Journal of Ecohumanism, 2024)
The current study aimed to investigate Artificial Intelligence experts' perceptions on the effective use of artificial intelligence applications in university learning environments. To achieve this, a purposive sample of 33 AI experts from four Arab countries (the UAE, Saudi Arabia, Jordan, and Bahrain) was selected. Data were collected using a qualitative research methodology, specifically through semi-structured interviews, after ensuring the validity and reliability of the tool. Qualitative research steps, including the grounded theory approach, were employed for data collection and analysis. The study revealed that AI experts emphasized the importance of integrating a range of artificial intelligence applications in university learning environments. These applications include implementing automated assessment, utilizing augmented and virtual reality, employing smart educational tools, leveraging personalized learning, applying adaptive learning, utilizing academic data analytics, and supporting academic research. The study also recommended the adoption of these applications in university education environments to enhance learning outcomes and overall effectiveness.